Membangun Literasi dalam Program Sustained Silent Reading di Kelas Semantik - Aliva Rosdiana (Universitas Islam Nahdlatul Ulama Jepara, 2017)
This study aims to describe how is SSR program able to increase students understanding and productivity particularly dealing with Semantics learning. This study was using quasi-experiment to prove the effectiveness with ratio test or ratio with two treatments, namely pre-treatment and post-treatment. SSR activity is conducted previously before lecturing class. During the fourth meeting in classroom, SSR activity is conducted and then in the fifth meeting they have post-test to investigate the result and the ratio. After post-test, the average score is achieved 72 or B. It is as evidence that the affect of improvement from SSR activity is increasing significantly even though it can’t be categorized perfect or score 100.